Redesain Logo dan Perancangan Brand Guideline terhadap The Quadrant Hotel - Andini Solim; Muhammad Fikri Akbar Zuhdi; Rizka Alya Triztika (Kartala Virtual Studies, 2026)
The Quadrant Hotel requires a consistent visual identity to strengthen its professional image across various communication media and enhance its brand competitiveness in the hospitality industry. Problems identified include a visually inefficient logo, inconsistent color usage, typography lacking fixed guidelines, the absence of structured supporting visual elements, and the lack of brand guidelines as a reference for implementing the visual identity. These conditions result in the brand identity being less than optimal in building a strong and easily recognizable impression among the public and hotel guests. This study aims to redesign the logo and develop The Quadrant Hotel's Brand Guidelines to make the visual identity simpler, more modern, elegant, easily recognizable, and can be applied consistently across various media. The method used is Design Thinking through the stages of observation, survey, visual analysis, concept formulation, design planning, implementation, and evaluation. The design results in a new logo with a clover concept that represents unity, balance, comfort, and the character of the hotel. The visual identity is supported by the main color with gold nuances, Baskerville and Poppins typography, and visual elements based on the logo shape that strengthens brand consistency. All elements are compiled in a Brand Guideline and applied to the company profile, amenities, administrative media, and promotional media. The findings proves the logo redesign and Brand Guideline design were able to create a visual identity for The Quadrant Hotel that is more consistent, professional, representative, and consistent along with characteristics of the modern hospitality industry.